Deletion in KRT75L4 linked to frizzle feather in Xiushui Yellow Chickens. (13th December 2021) - Chen, B.; Xi, S.; El‐Senousey, H. K.; Zhou, M.; Cheng, D.; Chen, K.; Wan, L.; Xiong, T.; Liao, M.; Liu, S.; Mao, H.
Summary: Bird feathers are the product of interactions between natural and artificial selection. Feather‐related traits are important for chicken selection and breeding. Frizzle feather is characterized by the abnormally development of feathers in chickens. In the current study, frizzle feather characteristics were observed in a local breed called Xiushui Yellow Chicken in Jiangxi, China. To determine the molecular mechanisms that underlie frizzle feather in Xiushui Yellow Chicken, four populations of three breeds (Xiushui Yellow Chicken with frizzle feathers, Xiushui Yellow Chicken with normal feathers, Guangfeng White‐Ear Yellow Chicken, and Ningdu Yellow Chicken) were selected for whole‐genome resequencing. Using a comparative genome strategy and genome‐wide association study, a missense mutation (g.5281494A>G) and a 15‐bp deletion (g.5285437‐5285451delGATGCCGGCAGGACG) in KRT75L4 were identified as candidate mutations associated with frizzle feather in Xiushui Yellow Chicken. Based on genotyping performed in a large Xiushui Yellow Chicken population, the g.5285437‐5285451delGATGCCGGCAGGACG mutation in KRT75L4 was confirmed as the putative causative mutation of frizzle feather. These results deepen the understanding of the molecular mechanisms responsible for frizzle feather, as well as facilitating the molecular detection and selection of the feather phenotype in Xiushui Yellow Chickens.